Migration, remittances, and inequality - Tan, Elizabeth S.; Lanzona, Leonardo A., Jr. (2009)
In the Philippines, domestic and international migration domestic are due to the pull of agglomeration economies. While the former is also driven by poverty, the latter is not but the result of two-step self selection process whereby the better-skilled and educated domestic migrants are also come from agglomeration economies. However, international migration produces the possibility of mitigating regional poverty because of the role of remittances.
Keywords: Labor migration; Migrant remittances; Migrant remittances -- Philippines